The Effectiveness of Guided Imagery Training on Anxiety of Competing Basketball Students at University - Sufitriyono; Aziz, Muhammad Ivan Miftahul; Jahrir, Andi Sahrul (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Competition anxiety is a psychological phenomenon that is often experienced by athletes/students, including basketball athletes/students, at the State University of Makassar and can have a negative impact on their performance on the field. This research is motivated by the need to find effective methods for overcoming such anxiety. The purpose of this study is to explore the effectiveness of guided imagery training in reducing competition anxiety in basketball athletes/students. The method used in this study is a quasi-experimental design with a pre-test and post-test approach. A total of 22 basketball students were selected by purposive sampling as research samples. Assessment of anxiety levels was carried out using the Scale of Anxiety (SA), which consists of 20 items, before and after the training intervention. The results of the data analysis showed that there was a significant decrease in athletes/students' level of anxiety after participating in guided imagery training; the t value obtained was 25.27, and the p value was 0.00 <0.05. This data indicates that this intervention not only aids in reducing anxiety but also has the potential to boost athletes/students' confidence. The conclusion of this study states that guided imagery training is proven to be effective in reducing competition anxiety in State University of Makassar basketball athletes/students. This study suggests that this method should be integrated into training programs to help athletes/students deal with the pressure of competition and increase their confidence.